2009
DOI: 10.1590/s0047-20852009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior and body image among psychology students

Abstract: objective: To characterize eating habits and possible risk factors associated with eating disorders among psychology students, a segment at risk for eating disorders. method: This is a cross-sectional study. The questionnaires Bulimic Investigatory Test Edinburgh (BITE), Eating Attitudes Test (EAT-26), Body Shape Questionnaire (BSQ) and a variety that considers related issues were applied. Statistical Package for the Social Sciences (SPSS) 11.0 was utilized in analysis. The study population was composed of 175… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
26

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 22 publications
2
16
0
26
Order By: Relevance
“…27 Regarding the association between perceived body image and BMI, our study identified that overweight/ obesity was associated with the desire to reduce the silhouette. This finding corroborates previous studies 6,10,28 and shows that the ideal body image among university students reflects the same slim and muscled patterns (for females and males, respectively) currently praised in sociocultural contexts, where fat or a higher body weight are seen as a stigma of ugliness, causing individuals with a higher BMI to feel uncomfortable and concerned with their body image. This finding is especially important if we take into consideration that BMI has been shown to strongly influence the adoption of abnormal behaviors, anorexia, bulimia, and vigorexia: even after adjustment for socioeconomic and demographic variables, the risk of developing such behaviors was two-fold higher in subjects with a BMI ≥ 25.0 kg/m².…”
Section: Discussionsupporting
confidence: 90%
“…27 Regarding the association between perceived body image and BMI, our study identified that overweight/ obesity was associated with the desire to reduce the silhouette. This finding corroborates previous studies 6,10,28 and shows that the ideal body image among university students reflects the same slim and muscled patterns (for females and males, respectively) currently praised in sociocultural contexts, where fat or a higher body weight are seen as a stigma of ugliness, causing individuals with a higher BMI to feel uncomfortable and concerned with their body image. This finding is especially important if we take into consideration that BMI has been shown to strongly influence the adoption of abnormal behaviors, anorexia, bulimia, and vigorexia: even after adjustment for socioeconomic and demographic variables, the risk of developing such behaviors was two-fold higher in subjects with a BMI ≥ 25.0 kg/m².…”
Section: Discussionsupporting
confidence: 90%
“…O ingresso na vida universitária provoca alterações no comportamento alimentar 13 , e a exposição ao novo meio social pode trazer como consequência aumento da insatisfação corporal. Estudos têm sido realizados no sentido de avaliar a insatisfação com o corpo e também as atitudes alimentares inadequadas em universitários [14][15][16] , porém a associação da checagem corporal com essas variáveis ainda é pouco explorada pelos pesquisadores.…”
Section: Introductionunclassified
“…Até o limite do nosso conhecimento, 23 estudos nacionais utilizaram o EAT-26 para rastrear comportamentos de risco para transtornos alimentares. Desses, um avaliou mulheres de 12 a 29 anos (com uma frequência de 16,5% de escore positivo) 7 , um investigou mães de filhas com e sem transtornos alimentares 40 , 12 analisaram amostras de universitárias [24][25][26][27][28][29][30][31][32][33][34][35] , seis avaliaram crianças e adolescentes 8,10,12,13,15,22 e três analisaram atletas 38,39,43 . A frequência de escore positivo encontrada no presente estudo é superior à da maioria dos estudos publicados até então.…”
Section: Discussionunclassified
“…Contudo, a amostra da maioria deles foi composta por crianças e adolescentes [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ou por estudantes universitários [24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Apenas um estudo avaliou gestantes 41 , porém, até o limite do nosso conhecimento, nenhum estudo nacional de base populacional avaliou tais fenômenos especificamente entre mães que não estejam grávidas.…”
Section: Introductionunclassified
See 1 more Smart Citation